The Impact Of Financial Markets Depth On Economic Growth In GCC Countries - Samer A. Abd; Yamen M. Debs (Educational Administration: Theory and Practice, 2024)
This research aims to study the impact of financial market depth on achieving economic growth in the Gulf Cooperation Council (GCC) countries during the period 2000-2019 using annual panel data. The study used the composite index of financial market depth approved by the International Monetary Fund, which includes multiple measures to assess the size and liquidity of the financial market, as an independent variable. The natural logarithm of GDP per capita was used as a dependent real variable. Foreign direct investment, technological development, and oil price logarithm were used as control variables, Panel data cointegration tests (Pedroni-Kaw-Fisher) were conducted to study the long-term equilibrium relationship between the variables. The Vector Error Correction Model (VECM) was then applied to estimate long and short-term parameters. Finally, the Granger Causality test was applied to confirm the presence of causal relationship, The study found a long-term equilibrium relationship between the variables based on the results of three tests (Kaw-Fisher). There was a significant positive effect of financial market depth on economic growth in the long term. As for the short term, there was a non-significant positive effect of financial market depth in the previous year on economic growth and a significant negative effect in the year before the previous. Regarding causal relationship, it was absent according to the Granger Causality test.